Rancang Bangunan Sistem Informasi Kasir Berbasis Web Pada Toko Acong CS Motor - Arya Sigit; Fikri Riduan; Nur Illahi Septa; Saprudin (Shofanah Media Berkah, 2023)
Abstract Based on the results of the research conducted, it was found that employees at the Acong CS Motor shop knew that there was a cashier website application that could make it easier to recap sales data every month and see what types of motorbikes were available in the showroom. Employees' knowledge of the cashier's application / website does not understand the functions and how to use it because previously there was no use of the cashier's website application in the showroom. sales every month and see what types of motorbikes are available in the showroom.